Mainland passage : the cultural anomaly of Puerto Rico - Soto-Crespo, Ramón E. (University of Minnesota Press, 2009)
One-third of the population of Puerto Rico moved to New York City during the mid-twentieth century. Since this massive migration, Puerto Rican literature and culture have grappled with an essential change in self-perception. Mainland Passage examines the history of that transformation, the political struggle over its representation, and the ways it has been imagined in Puerto Rico and in the work of Latina/o fiction writers. Ramón E. Soto-Crespo argues that the most significant consequence of this migration is the creation of a cultural and political borderland state. He intervenes in the Puert.